The US, the UN and the Korean War : Communism in the Far East and the American struggle for hegemony in the Cold War - Barnes, Robert John Reneʹ (Library of modern American history, 2014)
This study explores the fluctuating relationships, the tensions between Washington and its British Commonwealth allies and their impact on the development of the Korean conflict, from its outbreak in 1950 to its end at the Geneva Conference of 1954. Robert Barnes reframes the Korean War for the first time in the context of a United States less dominant than is usually imagined.